2015
DOI: 10.2174/1381612822666151112153351
|View full text |Cite
|
Sign up to set email alerts
|

Antiatherosclerotic and Cardioprotective Effects of Time-Released Garlic Powder Pills

Abstract: Garlic is believed to produce beneficial changes in different cardiovascular risk factors, thus possessing antiatherosclerotic properties. The hypotensive and cholesterol-lowering effects were investigated in two studies in men with mild arterial hypertension and in men with mild hypercholesterolemia. Eight-week treatment resulted in the reduction of both systolic and diastolic blood pressure by 5.2% (P=0.008) and 4.0% (P=0.014), respectively. In hypolipidemic study, the 12-week treatment resulted in a decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 131 publications
0
23
0
Order By: Relevance
“…It has been shown that Allium containing vegetables, especially garlic, possess very high antioxidant activities (Halliwell et al, 1992;Kinalski and Noreña, 2014;Locatelli et al, 2017;Zhang et al, 2015), with various bioactivities such as antifungal (Fratianni et al, 2016;Li et al, 2014;Yoshida et al, 1987), antiviral (Weber et al, 1992), antibacterial (Brown et al, 2013;Yoshida et al, 1999), hypoglycemic (Liu et al, 2007;Ryan et al, 2001), hyperglycemic (Hou et al, 2010;Moradi et al, 2013), hypolipidemic (Bordia et al, 1998) and anti-atherosclerotic activities (Ashraf et al, 2005;Karagodin et al, 2016). Furthermore, recent studies have associated garlic consumption with preventive effects on human cancer (Chiavarini et al, 2016;de Giorgio and Stebbing, 2016;Kaschula et al, 2016;Myneni et al, 2016;Saud et al, 2016;Smith et al, 2016).…”
Section: Bioactivity Perspectives and Applications Of Allium Sulfur mentioning
confidence: 99%
“…It has been shown that Allium containing vegetables, especially garlic, possess very high antioxidant activities (Halliwell et al, 1992;Kinalski and Noreña, 2014;Locatelli et al, 2017;Zhang et al, 2015), with various bioactivities such as antifungal (Fratianni et al, 2016;Li et al, 2014;Yoshida et al, 1987), antiviral (Weber et al, 1992), antibacterial (Brown et al, 2013;Yoshida et al, 1999), hypoglycemic (Liu et al, 2007;Ryan et al, 2001), hyperglycemic (Hou et al, 2010;Moradi et al, 2013), hypolipidemic (Bordia et al, 1998) and anti-atherosclerotic activities (Ashraf et al, 2005;Karagodin et al, 2016). Furthermore, recent studies have associated garlic consumption with preventive effects on human cancer (Chiavarini et al, 2016;de Giorgio and Stebbing, 2016;Kaschula et al, 2016;Myneni et al, 2016;Saud et al, 2016;Smith et al, 2016).…”
Section: Bioactivity Perspectives and Applications Of Allium Sulfur mentioning
confidence: 99%
“…Garlic simultaneously has a pungent smell and a spicy taste because of its organosulfur compounds (OSCs). The OSCs in garlic have been extensively investigated for their therapeutic applications (Arreola et al, ; Foroutanrad, Hazrati, & Khademvatan, ; Guan, Zhao, Xie, & Zeng, ; Karagodin, Sobenin, & Orekhov, ; Puccinelli & Stan, ). Alliin (S‐allyl‐L‐cysteine sulfoxide) is one of the major sulfur‐containing compounds in garlic (Hirsch et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Garlic (Allium sativum L.) possesses multiple antiatherosclerotic effects. Allicor, garlic powder, inhibits inflammation signaling (like TNF, IL-1b, ICAM-1, and HLA-DR expression and secretion) (Karagodin et al, 2016a). Garlic also exhibits hypotensive activity through the inhibition of angiotensin-converting enzyme (Asdaq and Inamdar, 2010), positive activation of the growth suppressor p27, descent of ERK1/2 phosphorylation (Castro et al, 2010), and downregulation of angiotensin II receptor (Mansour et al, 2013), reduction of vasoconstrictor prostanoids synthesis (Al-Qattan et al, 2001), stimulation of hydrogen sulfide (H2S) production (Al-Qattan et al, 2006), and regulation of endothelial nitric oxide (NO) synthesis (Ried and Fakler, 2014;Karagodin et al, 2016a).…”
Section: Possible Anti-atherosclerotic Mechanisms Of Medicinal Plantsmentioning
confidence: 99%
“…Allicor, garlic powder, inhibits inflammation signaling (like TNF, IL-1b, ICAM-1, and HLA-DR expression and secretion) (Karagodin et al, 2016a). Garlic also exhibits hypotensive activity through the inhibition of angiotensin-converting enzyme (Asdaq and Inamdar, 2010), positive activation of the growth suppressor p27, descent of ERK1/2 phosphorylation (Castro et al, 2010), and downregulation of angiotensin II receptor (Mansour et al, 2013), reduction of vasoconstrictor prostanoids synthesis (Al-Qattan et al, 2001), stimulation of hydrogen sulfide (H2S) production (Al-Qattan et al, 2006), and regulation of endothelial nitric oxide (NO) synthesis (Ried and Fakler, 2014;Karagodin et al, 2016a). Garlic antithrombotic activity revealed through suppression of cyclooxygenase (Ali et al, 2000), diminished production of thromboxane B2 and vasoconstrictors like prostaglandin E2 and leukotriene C4 by platelets (Vilahur and Badimon, 2013), control of membrane phospholipases activity, and serotonin and coagulation factor IV secreting from platelets (Rahman, 2007).…”
Section: Possible Anti-atherosclerotic Mechanisms Of Medicinal Plantsmentioning
confidence: 99%
See 1 more Smart Citation